Effects of Walking Pattern-Based Intelligent Electrical Stimulation on Outpatients with Stoke： A Randomized Controlled Study - HE Xuguang; SUN Wei; ZHOU Lu; HE Meiyan; WEI Ni (康复学报)
ObjectiveTo explore the effects of walking pattern based intelligent electrical stimulation on lower limb function in out-patients with stroke.MethodsA total of 60 outpatients with stroke who met the inclusion criteria were randomly divided into real stimulation group, sham stimulation group and control group. Finally, 52 patients completed the evaluation, including 20 patients in the control group, 15 patients in the sham stimulation group and 17 patients in the real stimulation group. All patients in the three groups received routine outpatient rehabilitation treatment and home rehabilitation guidance. The control group was not given electrical stimulation. The real stimulation group received walking pattern-based intelligent electrical stimulation once a day for 10 minutes, once a day, five days a week, with a duration of 8 weeks. The stimulation electrodes were placed on the active points of lower limb muscles (quadriceps femoris, hamstring muscle, tibialis anterior and gastrocnemius) on the hemiplegic side. The stimulation frequency was 30 Hz, the wavelength was 200 μs, and the intensity was the minimum intensity of muscle contraction. The stimu- lation electrodes placed in the sham stimulation group were the same with the real stimulation group, and the intensities could only cause weak sensory stimulation but no real muscle contraction. Lower limb function was assessed by Fugl-Meyer assessment (FMA), and balance function was assessed by postural assessment scale for stroke (PASS) and Berg balance scale (BBS). In addition, the walking ability was assessed by time up and go test (TUGT). The differences were compared among the three groups before the treatment and 2, 4 and 8 weeks posttreatment.ResultsThere was no significant difference in the baseline data and the evaluation results of the three groups before treatment. After 2 weeks treatment, the scores of FMA were significantly better than those before treatment in three groups (P<0.05). After 4 and 8 weeks treatment, the scores of FMA, PASS and BBS were significantly higher than those before treatment in the real stimulation group (P<0.05). After 2, 4 and 8 weeks treatment, the scores and improvement ratios of FMA, PASS and BBS were significantly different between the real stimulation group and the sham stimulation group or the control group (P<0.05). Besides, TUGT decreased more significantly in the real stimulation group than that of the sham stimulation group and the control group (P<0.05). That meaned that the stimulation group showed significant improvement in lower limb motor function, balance function, and walking ability compared to the control group and the sham stimulation group.ConclusionAfter discharge, hemiplegic outpatients after stroke receiving intelligent walking therapy could significantly improve the lower limb function, balance and walking ability.